Real-world effectiveness of antipsychotic medication in relapse prevention after cannabis-induced psychosis - Mustonen, Antti; Taipale, Heidi; Denissoff, Alexander; Ellilä, Venla; Di Forti, Marta; Tanskanen, Antti; Mittendorfer-Rutz, Ellenor; Tiihonen, Jari; Niemelä, Solja (CAMBRIDGE UNIV PRESS, 2025)
Background Cannabis use is linked to treatment non-adherence and relapses in psychotic disorders. Antipsychotic medication is effective for relapse prevention in primary psychoses, but its effectiveness after cannabis-induced psychosis (CIP) remains unclear.
Aims To examine the effectiveness of antipsychotic medication for relapse prevention following the first clinically diagnosed CIP.
Method A cohort of 1772 patients (84.1% men) with incident CIP was identified from the Swedish National Patient and Micro Data for Analyses of Social Insurance registers. The primary outcome was hospitalisation due to any psychotic episode. Drug use data were collected from the Prescribed Drug Register and modelled into drug use periods using the PRE2DUP method. A within-individual Cox regression model was used to study the risk of outcomes during the use of different oral or long-acting injectable (LAI) antipsychotics compared with non-use.
Results The mean age at first diagnosis was 26.6 years (s.d. = 8.3). Of the cohort, 1343 (75.8%) used antipsychotics and 914 (51.3%) experienced psychosis hospitalisation during the follow-up. Any antipsychotic use was associated with a decreased risk of psychosis hospitalisation (adjusted hazard ratio (aHR) 0.75; 95% CI 0.67-0.84). Specific antipsychotics associated with decreased risk included aripiprazole LAI (aHR 0.27; 95% CI 0.14-0.51), olanzapine LAI (aHR 0.28; 95% CI 0.15-0.53), clozapine (aHR 0.55; 95% CI 0.34-0.90), oral aripiprazole (aHR 0.64; 95% CI 0.45-0.91), antipsychotic polytherapy (aHR 0.74; 95% CI 0.63-0.87) and oral olanzapine (aHR 0.81; 95% CI 0.69-0.94).
Conclusions In particular, LAIs, clozapine and oral aripiprazole were associated with a decreased risk of psychosis relapse following CIP. Prescribers should consider using more LAIs for better treatment outcomes after CIP.